2021
DOI: 10.3390/ijms22168718
|View full text |Cite
|
Sign up to set email alerts
|

Physalin A, 13,14-Seco-16, 24-Cyclo-Steroid, Inhibits Stemness of Breast Cancer Cells by Regulation of Hedgehog Signaling Pathway and Yes-Associated Protein 1 (YAP1)

Abstract: The Hedgehog (HH) signaling pathway plays an important role in embryonic development and adult organ homeostasis. Aberrant activity of the Hedgehog signaling pathway induces many developmental disorders and cancers. Recent studies have investigated the relationship of this pathway with various cancers. GPCR-like protein Smoothened (SMO) and the glioma-associated oncogene (GLI1) are the main effectors of Hedgehog signaling. Physalin A, a bioactive substance derived from Physalis alkekengi, inhibits proliferatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 59 publications
(65 reference statements)
1
11
0
Order By: Relevance
“…Physalins B and F are potent inhibitors of GLI-1 among PANC1 (pancreatic cancer) cells ( Hosoya et al, 2008 ; Peukert and Miller-Mosilin, 2010 ), possibly by a mechanism associated with the inhibition of Hedgehog proteins, thus causing the interruption of the binding of GLIs to DNA (effector of Hedgehog signaling) ( Jiang and Hui, 2008 ). Ko et al (2021) found similar findings with physalin A in in vitro models of breast cancer, observing the inhibition of cancer cell proliferation/migration and mammosphere formation, associated with reduced expression of SMO and GLI1/2 proteins.…”
Section: Anticancer Activitysupporting
confidence: 71%
“…Physalins B and F are potent inhibitors of GLI-1 among PANC1 (pancreatic cancer) cells ( Hosoya et al, 2008 ; Peukert and Miller-Mosilin, 2010 ), possibly by a mechanism associated with the inhibition of Hedgehog proteins, thus causing the interruption of the binding of GLIs to DNA (effector of Hedgehog signaling) ( Jiang and Hui, 2008 ). Ko et al (2021) found similar findings with physalin A in in vitro models of breast cancer, observing the inhibition of cancer cell proliferation/migration and mammosphere formation, associated with reduced expression of SMO and GLI1/2 proteins.…”
Section: Anticancer Activitysupporting
confidence: 71%
“…A recent study showed that GLI1 inhibition reduced mammosphere formation of breast cancer cells. Interestingly, GLI1 inhibition resulted in a decrease in expression of YAP1, a Hippo pathway effector, suggesting a regulation activity of HH signaling on the Hippo pathway 148 …”
Section: Signaling Pathways Regulating Cscsmentioning
confidence: 99%
“…Interestingly, GLI1 inhibition resulted in a decrease in expression of YAP1, a Hippo pathway effector, suggesting a regulation activity of HH signaling on the Hippo pathway. 148 …”
Section: Signaling Pathways Regulating Cscsmentioning
confidence: 99%
See 1 more Smart Citation
“…FAK can regulate YAP/TAZ activation (163). Aberrant regulation of signaling pathways, such as ERa, Notch and Hedgehog, can lead to abnormal activation of Hippo, resulting in BCSC fate perturbations (164)(165)(166). The cumulative effect of aberrant regulation of these pathways in breast cancer maintains and enhances the characteristics of BCSCs, ultimately culminating in malignant tumor progression.…”
Section: Intertwining Of Signaling Pathways In Bcscsmentioning
confidence: 99%